Defect Detection in Fuel Cell Gas Diffusion Electrodes Using Infrared Thermography. Issue 2 (11th March 2016) - Ulsh, M.; Porter, J. M.; Bittinat, D. C.; Bender, G.
Abstract: Polymer electrolyte membrane fuel cells are energy conversion devices that offer high power densities and high efficiencies for mobile and other applications. Successful introduction into the marketplace requires addressing cost barriers such as production volumes and platinum loading. For cost reduction, it is vital to minimize waste and maximize quality during the manufacturing of platinum‐containing electrodes, including gas diffusion electrodes (GDEs). In this work, we report on developing a quality control diagnostic for GDEs, involving creating an ex situ exothermic reaction on the electrode surface and using infrared thermography to measure the resulting temperature profile. Experiments with a moving GDE containing created defects were conducted to demonstrate the applicability of the diagnostic for real‐time web‐line inspection.